Analisis Petrografi Fasa Molybdenum (Mo) dari Oksida Primer Fe2O3 Deposit Bontocani dengan Teknik X-Ray Mapping dan Difraksi Sinar-X - Subaer S; Nurhayati N; Nurhasmi N; Nurfadillah N (Department of Physics, Sebelas Maret University, 2017)
A researh related to petrogaphy analysis of molybdenum (Mo) has been conducted. The main objective of this study is to get quantitative information about the composotion of molybdenum (Mo) as a minor phase of primer mineral Fe2O3 deposited at Bontocani, District of Bone South Sulawesi. The petrography analysis was performed on 10 samples by means of Tescan Vega3SB Scanning Electron Microscopy (SEM) coupled with Bruker X-Ray Mapping and Energy Dispersive Spectroscopy (EDS). Crystallinity level and chemical composition(phase) mineral constituent were performed by using MiniFlexII X-Ray Diifraction (XRD). The petrography analysis in the form of elemental mapping show the position of Mo along with Fe, S and other elements. The XRD analysis showed that that the Mo mineral of Bontocani deposit is found in the form of pure Mo element with a concentration of 0.2 – 8.0 wt%, compound of Fe17(Mo3)0.1 and Fe2(MoO4)3 with a concentration of 2.04 wt% and 14.0 wt%.